PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN STRES GURU TERHADAP KINERJA GURU SMK NEGERI DI KOTA LUBUKLINGGAU - Eriani Eriani (Manajer Pendididikan, 2015)
The research in this research aims to find out: the influence of leadership principal and job stress teacher for performance improvement vocational high school teachers in lubuklinggaucity. This study is a surve casual. Collecting data using questionnaires and documentation. Analysis technique used is a simple regression analysis and analysis of double regreasi. Based on the research results can be concluded as follows: (1) a significant principal leadership on teacher performance improvement; (2) Teacher job stress significant on teacher performance improvement; (3) leadership principal and teachers working stress significant effect on teacher performance improvement.Keyword: leadership, job stress, and performance.